ROLE OF COMPANY SIZE IN MEDIATION PROFITABILITY OF CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE - Zulfa Rosharlianti; Dea Annisa; Novi Akhsani (EAJ (Economic and Accounting Journal), 2020)
The purpose of this study is to determine whether company size is able to mediate the effect of profitability on CSR (corporate social responsibility) disclosure. The population of this research is companies listed as companies in Indonesia which are listed on the IDX from 2017 to 2018. The sample selection uses a purposive sampling method, which amounts to 38 data. The analysis method in this study used path analysis with the help of the IBM SPSS Statistics version 22 program. The results of the study prove that profitability has no effect on company size. Profitability affects the disclosure of CSR. The size of the company does not affect the disclosure of corporate social responsibility. And company size does not mediate the relationship between profitability and CSR.